Studi in Silico dari Senyawa Turunan Flavonoid pada Bahan Alam sebagai Terapi Antinyeri dan Inflamasi dalam Menghambat COX 2 - Balqis Khansa Rahmatillah; Anisa Humaira Pelupessy; Amelia Putri; Aisril Eka Pertiwi; Afiq Rabbani Majid; Muhamad Iqbal Rhamadianto (JURNAL RISET RUMPUN MATEMATIKA DAN ILMU PENGETAHUAN ALAM, 2025)
Inflammation is the body's natural biological response to tissue injury, infection, or other harmful stimuli. Inflammatory processes play an important role in maintaining the body's homeostasis, but excessive or chronic inflammation can trigger various degenerative diseases, including arthritis, cancer, and cardiovascular disorders. One of the main mediators of inflammation is the enzyme cyclooxygenase-2 (COX-2), which is in charge of converting arachidonic acid into pro-inflammatory prostaglandins. Inhibition of COX-2 activity is an important strategy in controlling inflammation. Selective COX-2 inhibitors (Coxibs) have been developed to reduce the gastrointestinal side effects commonly caused by conventional nonsteroidal anti-inflammatory drugs (OAINS). However, the use of Coxibs still poses a significant cardiovascular risk, so the search for alternatives from natural ingredients continues. Flavonoid compounds, which are abundant in fruits, vegetables, teas, and spices, show great potential as natural COX-2 inhibitors. Flavonoids have a polyphenol structure that allows for strong interactions with COX-2 active sites through hydrogen bonding and hydrophobic forces. This study is a literature review that examines the potential of flavonoids from natural ingredients as COX-2 inhibitors based on an in silico approach. This method was carried out through a literature search on the Google Scholar database using the keywords "Flavonoid", "COX-2", "In Silico", "Molecular Docking", and "Anti-inflammatory". The results of the analysis of ten articles showed that compounds such as myricetin, quercetin, rutin, catechin, and epicatechin-3-O-gallate have a high bonding affinity with COX-2, even exceeding in some cases standard drugs such as diclofenac and dexamethasone. Low bond energy values (ΔG) and optimal amount of hydrogen bonds support this potential. The findings indicate that flavonoids from natural ingredients can be developed into candidates for selective anti-inflammatory drugs COX-2 that are safer and more effective than existing synthetic therapies.